Predictors of asthma control in elderly patients. Issue 3 (June 2016) - Ban, Ga-Young; Trinh, Tu H.K.; Ye, Young-Min; Park, Hae-Sim
Abstract : Purpose of review: We are in the era of rapid aging of the global population. Elderly asthmatic patients have an increased frequency of hospitalization and a high mortality rate. In this review, we focus on comorbidities and treatment issues in terms of the predictors of asthma control in the elderly. Recent findings: Some frequent comorbidities, such as chronic obstructive pulmonary disease, chronic sinusitis, obesity, and depression, are associated with uncontrolled asthma in elderly asthmatic patients. Smoking status in elderly asthmatic patients was associated with more frequent exacerbations. Management of comorbidities should be taken into account when we treat elderly asthmatic patients. Low treatment adherence, which is common in elderly asthmatic patients, predicts poor asthma control status. A poor knowledge about asthma, cognitive function impairment, and inappropriate inhaler technique result in low treatment adherence. Polypharmacy is associated with low treatment adherence, adverse drug reactions, and drug-drug interactions, and it is supposed to be a predictor of asthma control. Summary: Multifactorial assessments, including comorbidities, treatment adherence, and polypharmacy, are important for better asthma control in elderly asthmatic patients. Further studies on the strategy for the management of elderly asthmatic patients in a real-world setting are warranted.